Pengaruh Capital Intencity, Likuiditas dan Ukuran Perusahaan Terhadap Tax Avoidance - Eka Maulana; Suri Mahrani; Roy Budiharjo (LPMP Imperium, 2021)
This research aims to find out the effect of Capital Intencity, Liquidity and Firm Size on Tax Avoidance. The type of data used is a secondary data, with the methodof collecting documentation data from the IDXwebsite (www.idx.co.id). The object of this research is a manufacture company who has been registered on the Indonesia Stock Exchange period 2018 -2019. Sample is taken using a purposive sampling method in companies that publish the required data for this research in their annual reports. From 195 manufacture companies that listed on IDX, only 147 companies who have a complete data to be researched for 2 periods, and there are 294 samples obtained. The statistical test used is the classic assumption test, the feasibility of model test. The result of this research showing that the Capital Intencity of the company will not affect tax avoidance. While the two other variables, who took part in the research Likuiditas and Firm Size simultaneously against tax avoidance.